KEMAMPUAN MEMAHAMI HUBUNGAN MAKNA DALAM KALIMAT PADA SISWA KELAS XI SMK PERSADA BANDAR LAMPUNG - Hastuti, Hastuti (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2020)
The ability to understand the meaning relationship is the ability to understand the relationship of meaning in sentences which include synonyms, antonyms, homonyms, homographs, homophones, hyponyms; hypernIM, and polysemia. This study aims to find out and describe how the level of students' ability to understand the relationship of meaning in sentences in the aspects above. The method used in this research is descriptive qualitative method, while the technique of collecting data is multiple choice objective test techniques. The population in this study amounted to 218 students and the study sample was set at 54 people. The sampling technique used is the stratified proportional random sampling technique. The results showed that overall, the level of ability to understand meaning relations in the sentence of class XI Even semester of SMK Persada Bandar Lampung was categorized enough with an average score of 68.59. For each aspect, the level of students' ability is as follows: ability of synonymy in good category (77%), ability to understand antonyms in good categories (73.59%), ability to understand homonyms in good categories (73.70), ability to understand homophones in good categories ( 72.18%), the ability to understand homographs is in the less category (50.35), the ability to understand hyponyms is in the good category (77.74%), the ability to understand hypernimms is in a sufficient category (62.33), and the ability to understand polysemi in the less category (59.62%).